EXPLORING THE PERCEPTION OF DENTAL TREATMENT THROUGH THE REPORTS OF RETTIE WILDING: A MISSIONARY PHYSICIAN IN THE FIRST HALF OF THE 20TH CENTURY (CIPEEX, 2026)
This study aims to analyze the reports of the Scottish missionary physician Henrietta Buchan Wilding (1889–1971), who graduated in Medicine from the University of Glasgow in 1923, as a historical and cultural source on dental treatment in the first half of the 20th century. Her work in Brazil, mainly in Goiás, took place in a context of inequality and extreme precariousness in oral health, marked by rudimentary practices, lack of prevention, and limited access to adequate dental care. The research, of a historical-descriptive nature, draws on a documentary analysis of the author’s memoir Sowing in Tears and a literature review on Brazilian dentistry of the period, highlighting the contrast between academic advances and the reality of marginalized populations. The results show that Wilding, in addition to performing emergency tooth extractions, sought to train nurses and local agents, promote educational campaigns, and organize resources in innovative ways, using accessible language to raise awareness about oral hygiene. Her practice went beyond clinical care, integrating science, spirituality, and social transformation, underscoring the importance of interdisciplinary and humanized approaches. It is concluded that her reports not only document the structural deficiencies of the time but also constitute a valuable historical heritage for understanding the evolution of dentistry in Brazil and the possible pathways toward culturally sensitive health practices.
Keywords: RETTIE WILDING; HISTORICAL DENTISTRY; MISSIONARY MEDICINE; DENTAL EDUCATION